2018
DOI: 10.29312/remexca.v9i4.1392
|View full text |Cite
|
Sign up to set email alerts
|

P-Ca, AG4/7 y 6-BAP en la fisiología y nutrición de tomate en invernadero

Abstract: El tomate es un cultivo de importancia mundial por su aportación en mano de obra, economía y calidad alimenticia. Estas características obligan a una continua búsqueda de tecnologías que contribuyan a mejorar el rendimiento y calidad del fruto. En este estudio se evaluó el efecto de biorreguladores en parámetros foliares, contenido de nutrientes, rendimiento y calidad del fruto en tomate saladette híbrido “Raptor-F1” en la UAAAN, Saltillo, Coahuila, durante abril-agosto de 2015, bajo condiciones de invernadero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It is well established that when exogenous GA 4 and GA 7 are applied, both hormones promote seed germination in tomato, pepper and several other crops [3,6,16]. GA 1 has also been reported as seed germination promoter in various horticultural species [16,7]. These three hormones move throughout different plant organs whereas GAs A 9 , A 15 , A 17 and A 44 are classified as biological inactive hormones [3,8,13,14,15].…”
Section: Flow Diagram Outlining Procedures Used For the Extraction And Purification Of Simmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that when exogenous GA 4 and GA 7 are applied, both hormones promote seed germination in tomato, pepper and several other crops [3,6,16]. GA 1 has also been reported as seed germination promoter in various horticultural species [16,7]. These three hormones move throughout different plant organs whereas GAs A 9 , A 15 , A 17 and A 44 are classified as biological inactive hormones [3,8,13,14,15].…”
Section: Flow Diagram Outlining Procedures Used For the Extraction And Purification Of Simmentioning
confidence: 99%
“…On the basis of results obtained in this research and previous data [14,17], it is possible to speculate as to which degree gibberellins may be involved in the germination process of habanero seeds. The rate of hydroxylation has been related to the movement of gibberellins [7]. Feeding labeled gibberellins to intact fruit has shown that some degree of hydroxylation is necessary for movement.…”
Section: Flow Diagram Outlining Procedures Used For the Extraction And Purification Of Simmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomato and hot pepper seed treatments with gibberellic acid and 6-benzyl amino purine in a range of 40-70 mg/L -1 have proved to increase germination percentage and seedling growth. The presence of endogenous gibberellins such as GA4, GA7 and GA9 are reported in apple seeds and have been related to an improvement in germination and seedling development [4]; however, the presence of gibberellins and cytokinins in tomato seeds is less documented [4,5]. Therefore, the aim of this study was to investigate the possible presence of endogenous gibberellins and cytokinins in saladette tomato seeds.…”
Section: Introductionmentioning
confidence: 99%